Adolescent Endometriosis: Diagnosis and Treatment Approaches (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Endometriosis is a chronic gynaecological disorder that affects a large number of adolescents, causing, dysmenorrhea and impaired quality of life. To evaluating diagnosis and treatment approaches for adolescent endometriosis. Materials and methods: This was a cross-sectional study 150 adolescent girl, aged 13 to 19, in purposively selected healthcare settings in Sylhet, including Jalalabad Ragib-Rabeya Medical College and Hospital, Oasis Hospital etc. Results: The participants had a mean age of 16.4 years, an average BMI of 22.6 kg/m², and an average age at menarche of 12.5 years. A family history of endometriosis was reported in 26.7% of cases. Diagnostic methods used included laparoscopy (66.7%), MRI (20.0%) and ultrasound (13.3%). Treatment strategies comprised hormonal therapy (73.3%), NSAIDs (60.0%), laparoscopic surgery (33.3%), complementary therapies (20.0%), psychological counseling (26.7%), and physical therapy (13.3%). The mean PedsQL score was 65.2, the EPDD score was 6.8 and the HADS score averaged 14.3. Half of the participants experienced delays in diagnosis, which significantly impacted timely treatment. Improved outcomes were associated with early menarche, hormonal therapy, and laparoscopic surgery. Conclusion: This study underscores the significant diagnostic delays and the profound impact of endometriosis on the quality of life of adolescents in Bangladesh. Enhancing diagnostic protocols, promoting early intervention, and strengthening support systems are essential for improving the management of adolescent endometriosis.Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 22-26